The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1016/0014-5793(90)81030-r
|View full text |Cite
|
Sign up to set email alerts
|

Purification and internal amino acid sequence of the 80 kDa protein kinase C substrate from Swiss 3T3 fibroblasts

Abstract: The acidic 80 kDa protein kinase C (PKC) substrate was purified from 2.3 x lw" Swiss 3T3 fibroblasts. Partial amino acid sequence data were obtained from five peptides generated by S. aureas V8 cleavage of the protein, enabling a total of 91 amino acid residues to be assigned. The sequences of these five peptides were compared to the deduced amino acid sequences of acidic SO-87 kDa PKC substrates from both actively proliferating A43 1 epidermal carcinoma cells, and fully differentiated neural tissue. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Use of the minimum reagent volumes possible with the current hardware design did not cause any sequencing failures, and each aliquot of R 1 (1 5 pL) still contained a large molar excess of PITC over the peptides or proteins analyzed. A more versatile method of microcartridge operation may be obtained by the use of integrated micropathways for fluid delivery, as has been recently described for a new compact sequencer by Calaycay et al (1991). The presentation of samples on a reduced surface area was found to improve the initial yields relative to the standard system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the minimum reagent volumes possible with the current hardware design did not cause any sequencing failures, and each aliquot of R 1 (1 5 pL) still contained a large molar excess of PITC over the peptides or proteins analyzed. A more versatile method of microcartridge operation may be obtained by the use of integrated micropathways for fluid delivery, as has been recently described for a new compact sequencer by Calaycay et al (1991). The presentation of samples on a reduced surface area was found to improve the initial yields relative to the standard system.…”
Section: Discussionmentioning
confidence: 99%
“…The revised operating programs described here have improved performance, productivity, and chemical consumption. Extensive analysis of a wide range of standard samples has revealed no inherent loss in the ability of the original sequencer to analyze both peptides and proteins with no obvious sequence-specific restrictions, and we have used the system routinely to determine the sequence of many novel peptides and proteins (Brooks et al, 1990;Kozma et al, 1990;Abo et al, 1991;Diekmann et al, 1991;Otsu et al, 1991). The increased sample turnover and sensitivity obtainable using these cycles now justifies the development of systems for multiple sample loading and very low picomole to femtomole analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same 80K protein is phosphorylated in cell-free systems either by activation of endogenous PKC or by addition of the purified enzyme [22,24]. Recently, this prominent PKC substrate has been purified to homogeneity from heatstable extracts of Swiss 3T3 cells [26]. The preparation is an effective substrate of PKC and contains an unusually high proportion of acidic amino acids and of alanine.…”
Section: Activation Of Pkc In Intact Fibroblastsmentioning
confidence: 99%
“…Surprisingly, the comparison of these amino acid sequences with the deduced amino acid sequence of the bovine brain substrate revealed that these proteins are closely related but are not identical (35% divergence). These PKC substrates do not exhibit significant homology to other cellular proteins [26,32]. Thus, it is well established that an increase in the phosphorylation of 80K in intact cells provides a specific marker for PKC activation.…”
Section: Activation Of Pkc In Intact Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation